2022
DOI: 10.3389/fnins.2022.960149
|View full text |Cite
|
Sign up to set email alerts
|

The Polycomb group gene rnf2 is essential for central and enteric neural system development in zebrafish

Abstract: The development of central nervous system (CNS) and enteric nervous system (ENS) is under precise and strict control in vertebrates. Whether and how the Polycomb repressive complex 1 (PRC1) is involved in it remain unclear. To investigate the role of PRC1 in the nervous system development, using CRISPR/Cas9 technology, we have generated mutant zebrafish lines for the rnf2 gene which encodes Ring1b, the enzymatic component of the PRC1 complex. We show that rnf2 loss of function leads to abnormal migration and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 75 publications
0
9
0
Order By: Relevance
“…PCGF1 deletion did not affect the basic formation of the ENS, including gut colonization by ENS precursors and total neuron numbers, suggesting that PCGF1 is dispensable for ENS precursor migration and enteric neurogenesis. In this respect, our study suggests that PCGF1 alone is not responsible for the rnf2-(PRC1) (Feng & Sun, 2022) or Aebp2/Ezh2-(PRC2) (Kim et al, 2011(Kim et al, , 2018 (Memic et al, 2018;Morarach et al, 2021;Wright et al, 2021), this study provides evidence, for the first time to our knowledge, that epigenetic mechanisms also regulate neuronal subtype specification. org/) (Oki et al, 2018), an open-access chromatin immunoprecipitation sequencing (ChIP-seq) database.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…PCGF1 deletion did not affect the basic formation of the ENS, including gut colonization by ENS precursors and total neuron numbers, suggesting that PCGF1 is dispensable for ENS precursor migration and enteric neurogenesis. In this respect, our study suggests that PCGF1 alone is not responsible for the rnf2-(PRC1) (Feng & Sun, 2022) or Aebp2/Ezh2-(PRC2) (Kim et al, 2011(Kim et al, , 2018 (Memic et al, 2018;Morarach et al, 2021;Wright et al, 2021), this study provides evidence, for the first time to our knowledge, that epigenetic mechanisms also regulate neuronal subtype specification. org/) (Oki et al, 2018), an open-access chromatin immunoprecipitation sequencing (ChIP-seq) database.…”
Section: Discussionmentioning
confidence: 54%
“…PCGF1 deletion did not affect the basic formation of the ENS, including gut colonization by ENS precursors and total neuron numbers, suggesting that PCGF1 is dispensable for ENS precursor migration and enteric neurogenesis. In this respect, our study suggests that PCGF1 alone is not responsible for the rnf2‐ (PRC1) (Feng & Sun, 2022) or Aebp2 / Ezh2‐ (PRC2) (Kim et al, 2011, 2018) deficient phenotypes whose disruption impairs ENS precursor migration and enteric ganglion formation, respectively. Pcgf1 deficiency specifically impaired Sst + neuron numbers in the multiple gut regions.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Recently one factor associated with chromatin modification, Ring finger protein 2 (Rnf2), has been discovered to impact zebrafish ENS formation [ 75 ]. Modifying histones to control chromatin state is another prominent way regulators exert epigenetic control over gene expression.…”
Section: Epigenetic Regulation Of Zebrafish Ens Developmentmentioning
confidence: 99%
“…The mammalian Polycomb repressive complex 1 contains the ubiquitin E3 ligase RING1, as either RING1A or RING1B, catalyzing the ubiquitination of Lys119 of histone H2A, largely a repressive mark [ 76 ]. Zebrafish mutants for rnf2 , with predicted homology to Ring1b , present colonic aganglionosis, intestinal hypoganglionosis, and a reduction in gut tube ENCCs [ 75 ]. Examination during early NCC specification stages in rnf2 mutants revealed that the zebrafish NCC specifiers foxd3 and sox9b were differentially reduced in expression amongst cranial, vagal, and trunk NCC domains, where sox9b exhibited a strong loss of expression in cranial NCC, while foxd3 was globally restricted.…”
Section: Epigenetic Regulation Of Zebrafish Ens Developmentmentioning
confidence: 99%